2012
DOI: 10.1038/nnano.2012.207
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecular coronas provide the biological identity of nanosized materials

Abstract: Publication informationNature nanotechnology, 7 (12): 779-786Publisher Nature Publishing Group Item record/more information

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
1,978
1
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 2,357 publications
(2,078 citation statements)
references
References 110 publications
36
1,978
1
11
Order By: Relevance
“…Numerous studies have shown that it is the biophysicochemical properties of the biomolecular corona, instead of properties of the pristine NPs, that determine the biological identity of the NPs in interacting with the biological system. 4 As a counterpart of the protein corona formed on NPs entering the blood vessels, the PS corona is acquired immediately and inevitably after NPs enter the respiratory system. Once the PS corona is formed on the NP surface, the biophysicochemical properties of the corona determine the further nano-bio interactions of the NPs, such as their bioavailability, biodistribution, retention, translocation, and clearance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have shown that it is the biophysicochemical properties of the biomolecular corona, instead of properties of the pristine NPs, that determine the biological identity of the NPs in interacting with the biological system. 4 As a counterpart of the protein corona formed on NPs entering the blood vessels, the PS corona is acquired immediately and inevitably after NPs enter the respiratory system. Once the PS corona is formed on the NP surface, the biophysicochemical properties of the corona determine the further nano-bio interactions of the NPs, such as their bioavailability, biodistribution, retention, translocation, and clearance.…”
Section: Resultsmentioning
confidence: 99%
“…50 Third, the PS corona coated on the pristine NP obviously increases the phosphate group density on the NP surface. Because the phosphate group plays a crucial role in the biorecognition of NPs, 4 the PS corona may lead to enhanced cellular uptake of the NPs. 28,30,49 Due to differential molecular conformations of the PS corona formed on the hydrophilic and hydrophobic NPs (Figures 2−5), the phosphate group on the Ag-NP shows a larger density than that on the PST-NP (Table 1), thus indicating an easier cellular uptake of the hydrophilic NPs than the hydrophobic NPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] However, NPs dispersed in a biological fluid are rapidly covered by biomolecules, such as proteins and lipids, forming a biomolecular 'corona' that effectively screens the bare NP surface. [17][18][19][20][21][22] When cells are exposed to NPs it is therefore, in realistic circumstances, typically not the bare NP surface that interacts with the cell but the NP-biomolecular corona complex. [23][24][25] Consequently, it becomes interesting to correlate NP uptake not to properties of the bare NP, but to properties of the NP-biomolecular corona complex.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 By changing nanoparticle properties and design, the profile of proteins adsorbed to their surfaces from the surrounding environment, such as for instance blood serum, is also changed. 35,36 It has been hypothesized that this layer (corona) of proteins on the nanoparticle surface affects much of the interactions with cells 37,38 and thus properties of the bare nanoparticle surface, such as charge, are less important for cellular interactions. Indeed initial evidence suggests that the capacity of nanoparticles to cross the BBB is connected to the nature of the proteins adsorbed on their surface, such as, for instance, apolipoproteins.…”
Section: Introductionmentioning
confidence: 99%